Periodic Solution for Impulsive Cellar Neural Networks with Time-Varying Delays in the Leakage Terms - Bingwen Liu; Shuhua Gong (Abstract and Applied Analysis)
This paper is concerned with impulsive cellular neural networks with time-varying delays in leakage terms. Without assuming bounded and monotone conditions on activation functions, we establish sufficient conditions on existence and exponential stability of periodic solutions by using Lyapunov functional method and differential inequality techniques. Our results are complement to some recent ones.